Statistical analysis for freeze–thaw resistance of cement mortars containing marble dust and glass fiber - Keleştemur, Oğuzhan; Yıldız, Servet; Gökçer, Bihter; Arici, Erdinç (My University, 2014)
This paper investigated the usability of marble dust and glass fiber against the harmful effects of freeze–thaw (FT) cycles on cement mortars as experimentally and statistically. To this end, the cement mortar specimens containing marble dust (0%, 20%, 40% and 50% by volume) and glass fiber (0 kg/m3, 0.25 kg/m3, 0.50 kg/m3, 0.75 kg/m3) were prepared. The compressive and flexural strengths of the specimens were determined after being exposed to FT cycles. In order to reduce the numbers of experiments, an L16 (42 21) Taguchi orthogonal array was adopted to the study. Amounts of glass fiber, percentages of marble dust and cycles of freeze–thaw, were changed to explore their effects on the compressive and flexural strengths of the mortar specimens. Statistically effects of the factors were also determined by using analysis of variance (ANOVA) method. Finally, experimental findings were compared with statistical results and a good agreement between them was achieved
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: glass fiber; resistance